2020
DOI: 10.1590/1806-9282.66.9.1235
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of sarcopenia in kidney transplants and their association with determinant factors of muscle homeostasis

Abstract: SUMMARY INTRODUCTION: Sarcopenia is characterized by the involuntary loss of lean body mass associated with a progressive reduction of muscle strength. OBJECTIVE: To determine the prevalence of sarcopenia in kidney transplant recipients and its association with the determining factors that control muscle homeostasis. METHODS: We evaluated renal transplant recipients undergoing follow-up at the University Hospital of the Federal University of Maranhão from June 2017 to July 2018 and who met the inclusion cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 10 publications
0
16
0
1
Order By: Relevance
“…Out of these, 20 studies were excluded for reasons detailed in Table S2 . Finally, 23 6 , 7 , 8 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 studies were included, involving 2535 KTRs with 59.7% of male subjects. Of these, nine studies were from Europe, seven were from Asia, five were from South America, one was from North America, and one was from Oceania.…”
Section: Resultsmentioning
confidence: 99%
“…Out of these, 20 studies were excluded for reasons detailed in Table S2 . Finally, 23 6 , 7 , 8 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 studies were included, involving 2535 KTRs with 59.7% of male subjects. Of these, nine studies were from Europe, seven were from Asia, five were from South America, one was from North America, and one was from Oceania.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, working on that same population, our group recently observed that approximately 19% of KTPs who attended an outpatient clinic suffered from sarcopenia [48]. In addition, a couple of recent cross-sectional studies have demonstrated important findings as to the prevalence of sarcopenia and poor prognosis based on its components in KTPs [31,32]. In one study, 11% of a sample consisting of 210 KTPs had sarcopenia [31], and 19% of 83 KTPs in the other [32].…”
Section: Discussionmentioning
confidence: 95%
“…In one study, 11% of a sample consisting of 210 KTPs had sarcopenia [31], and 19% of 83 KTPs in the other [32]. Regarding the latter, among individuals without sarcopenia, 18% had a decrease in HGS and 40% in altered gait speed, hence indicating that an individual evaluation of sarcopenia components should be taken into consideration as well [32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations